Management of Gustilo-Anderson Type II and IIIA Open Long Bone Fractures in Children: Which Wounds Require a Second Washout?. Issue 6 (July 2020) - Wang, Kemble K.; Rademacher, Emily S.; Miller, Patricia E.; Lins, Laura; Jordan, Eric; May, Collin; Glotzbecker, Michael P.; Hedequist, Daniel J.; Shore, Benjamin J.
Abstract : Introduction: Timing of wound closure in pediatric Gustilo-Anderson grade II and IIIA open long bone fracture remain controversial. Our aims are (1) to determine the proportion of patients with these fractures whose wounds can be treated with early primary wound closure (EPWC); (2) to compare the complication rates between EPWC and delayed wound closure (DWC); and (3) to determine factors associated with higher likelihood of undergoing DWC. Patients and Methods: At a level-1 pediatric trauma center, 96 patients (younger than 18 y) who sustained Gustilo-Anderson grade II and IIIA open long bone fractures (humerus, radius, ulnar, femur, or tibia) within a 10-year period (2006-2016) were included for this study. Decision for EPWC versus DWC was at the discretion of the attending surgeon at time of initial surgery. Data collection was via retrospective review of charts and radiographs. Particular attention was paid to the incidence of return to operating room rate, nonunion, compartment syndrome, and infection. Median follow-up duration was 7.5 months (interquartile range: 3.6 to 25.3 mo). All patients were followed-up at least until bony union. Results: Overall, 81% of patients (78/96) underwent EPWC. Of the grade II fractures, 86% underwent EPWC. Four patients (5%) in the EPWC group and 1 patient (6%) in the DWC group had at least 1 complication. When controlling for mechanism of injury, Gustilo-Anderson fracture type and age, there was no difference in rate of complications between the EPWC and the DWC groups. Grade IIIA fractures and being involved in a motor vehicle accident were factors associated with a higher likelihood of undergoing DWC. Conclusion: The majority of grade II and IIIA pediatric long bone fractures may be safely treatable with EPWC without additional washouts. Future prospective research is required to further define the subgroups that can benefit from DWC. Level of Evidence: Level IV—therapeutic, case cohort study. Abstract : Supplemental Digital Content is available in the text.